2008
DOI: 10.1038/sj.ejhg.5202002
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations in the NF1 gene region are infrequent and do not predispose to recurrent type-1 deletions

Abstract: Gross deletions of the NF1 gene at 17q11.2 belong to the group of 'genomic disorders' characterized by local sequence architecture that predisposes to genomic rearrangements. Segmental duplications within regions associated with genomic disorders are prone to non-allelic homologous recombination (NAHR), which mediates gross rearrangements. Copy number variants (CNVs) without obvious phenotypic consequences also occur frequently in regions of genomic disorders. In the NF1 gene region, putative CNVs have been re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Whereas most type-2 NF1 deletions are of postzygotic origin, the vast majority of type-1 NF1 deletions with breakpoints located within the NF1-REPs A and C are mediated by interchromosomal NAHR during maternal meiosis [Ló pez-Correa et al, 2000; Steinmann et al, 2008]. This mirrors the origin of the germline microdeletions underlying Williams-Beuren syndrome, DiGeorge syndrome, and Angelman syndrome, which are also predominantly generated by interchromosomal NAHR during either maternal or paternal meiosis [Thomas et al, 2006, and references therein].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas most type-2 NF1 deletions are of postzygotic origin, the vast majority of type-1 NF1 deletions with breakpoints located within the NF1-REPs A and C are mediated by interchromosomal NAHR during maternal meiosis [Ló pez-Correa et al, 2000; Steinmann et al, 2008]. This mirrors the origin of the germline microdeletions underlying Williams-Beuren syndrome, DiGeorge syndrome, and Angelman syndrome, which are also predominantly generated by interchromosomal NAHR during either maternal or paternal meiosis [Thomas et al, 2006, and references therein].…”
Section: Discussionmentioning
confidence: 99%
“…Two common types of recurrent NF1 deletion have been identified that differ in terms of their size and breakpoint location: type-1 NF1 deletions span 1.4-Mb and are mediated by NAHR between LCRs termed NF1-REP A and NF1-REP C [Dorschner et al, 2000;Jenne et al, 2001;Ló pez-Correa et al, 2001]. The majority of type-1 NF1 deletions are maternally inherited germ-line deletions [Ló pezCorrea et al, 2000;Steinmann et al, 2008;Upadhyaya et al, 1998] whose breakpoints are located within two hotspot regions of meiotic recombination termed PRS1 and PRS2 [Forbes et al, 2004;Ló pez-Correa et al, 2001]. By contrast, type-2 NF1 deletions encompass only 1.2-Mb and their breakpoints are located within the SUZ12 gene (MIM] 606245) and its pseudogene SUZ12P, which immediately flank the NF1-REPs (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mosaicism was also investigated in patients 3304 and 1860-M with NF1 deletions other than type-2. The breakpoints of the atypical deletion in patient 1860-M were previously identified [Steinmann et al, 2008] whereas the extent of the atypical or type-1 NF1 deletion of patient 3304 has been characterized in this study using FISH (Supp. Fig.…”
Section: Patients and Cell Linesmentioning
confidence: 97%
“…Two of these six patients had an inherited atypical deletion (patients 1860 and 1860-1) whereas four patients had sporadic NF1 deletions. The deletion in patient 1860 spans 1.3 Mb and is atypical [Steinmann et al, 2008;Supp. Fig.…”
Section: Patients and Cell Linesmentioning
confidence: 99%
“…Whereas the vast majority of type-1 deletions occur during maternal meiosis and therefore manifest as constitutional deletions in the offspring [Ló pez-Correa et al, 2000;Steinmann et al, 2008;Upadhyaya et al, 1998], type-2 NF1 deletions occur preferentially during early fetal mitotic cell divisions giving rise to somatic mosaicism Steinmann et al, 2007]. These somatic type-2 NF1 deletions therefore provide an ideal model system in which to study the genomic features that could serve to promote mitotic NAHR.…”
Section: Introductionmentioning
confidence: 99%